2016
DOI: 10.1016/j.ydbio.2016.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Spatial regulation of cell cohesion by Wnt5a during second heart field progenitor deployment

Abstract: Wnt5a, a non-canonical Wnt ligand critical for outflow tract (OFT) morphogenesis, is expressed specifically in second heart field (SHF) progenitors in the caudal splanchnic mesoderm (SpM) near the inflow tract (IFT). Using a conditional Wnt5a gain of function (GOF) allele and Islet1-Cre, we broadly over-expressed Wnt5a throughout the SHF lineage, including the entire SpM between the IFT and OFT. Wnt5a over-expression in Wnt5a null mutants can rescue the cell polarity and actin polymerization defects as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 46 publications
7
54
0
Order By: Relevance
“…Tbx1 is expressed in SpM in both the epithelial layer and adjacent mesenchyme. Previous reports have hypothesized a process of intercalation as a means of mesenchymal cells to contribute to the epithelial layer (15)(16)(17). However, this model still needs to be confirmed.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Tbx1 is expressed in SpM in both the epithelial layer and adjacent mesenchyme. Previous reports have hypothesized a process of intercalation as a means of mesenchymal cells to contribute to the epithelial layer (15)(16)(17). However, this model still needs to be confirmed.…”
Section: Discussionmentioning
confidence: 90%
“…Tbx1 has been shown to be required for progenitor recruitment to the heart (11,12) and its loss has been associated with disruption of epithelial polarity in the DPW (13), and reduced tension of the epithelial sheet (14), although the mechanisms by which these phenotypic anomalies occur remain unclear. Planar cell polarity (PCP) genes Dvl2 and Wnt5a have been proposed to be part of this process by facilitating the incorporation, by intercalation, of mesenchymal cells into the epithelial sheet of the DPW (15)(16)(17). TBX1 regulates Wnt5a expression in the SHF (18), suggesting that at least some of the tissue architectural roles of TBX1 may operate through the non-canonical WNT/PCP pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Oriented cell elongation and polarized actomyosin are predominantly observed in the pDPW, suggesting greater sensitivity to cell deformation. Indeed, increased basal lamina formation and epithelial cohesion due to the presence of E-cadherin and absence of Wnt5a expression has been reported in the aDPW as SHF cells approach the arterial pole of the heart1220.…”
Section: Discussionmentioning
confidence: 98%
“…The planar cell polarity gene Vangl2 regulates epithelial organization in SHF cells as they differentiate into outflow tract (OFT) myocardium at the arterial pole of the heart, and loss of Vangl2 leads to OFT septation defects19. Furthermore, increased epithelial cell cohesion in the anterior DPW (aDPW) has recently been proposed to create a pulling force that drives progenitor cell addition to the OFT20. Altogether, these studies identify the epithelial properties of cells in the DPW as a regulatory step in the control of proliferation, differentiation and deployment of cardiac progenitor cells.…”
mentioning
confidence: 99%
“…1A,B) (Cortes et al, 2018). For instance, it was reported that the Wnt5a-Disheveled (Dvl) planar cell polarity (PCP) signaling regulates epithelial conversion of the SHF progenitors in the SpM for cell deployment (Sinha et al, 2012;Li et al, 2016). This research also suggested that the core PCP gene Vangl2 is involved in this process.…”
Section: Introductionmentioning
confidence: 99%